2018
DOI: 10.17628/ecb.2018.7.42-51
|View full text |Cite
|
Sign up to set email alerts
|

Free and Zeolite-Immobilized Probiotic Mixture Versus Sodium Valproate in Prevention of Oxidative Stress and Modulation of the L-Arginine Intracellular Metabolic Pathways in the Rat Brain and Blood Following Dexamphetamine-Induced Bipolar D

Abstract: Institute of fine organic chemistry (FOC) of scientific technological center of organic and pharmaceutical chemistry NAS, Republic of Armenia EXPERIMENTAL Materials Depakine, containing sodium valproate (VPA) (Sanofi-Aventis U.S. LLC) as an active substance, d-amphetamine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…One study showed that probiotic treatment reduced the hippocampal oxidative stress (Chunchai et al, 2018). Five studies reported that probiotic supplementations attenuated oxidative enzymes (Sun et al, 2016;Alchujyan et al, 2018;Xu et al, 2018;Ramalho et al, 2019;Salami et al, 2019). Consistently, 4 studies showed that probiotic administration increases antioxidant activity (Divyashri et al, 2015;Huang et al, 2018;Ho et al, 2019;Roy Sarkar et al, 10.3389/fnins.2022.1065995 2020.…”
Section: Oxidant and Anti-oxidant Factorsmentioning
confidence: 92%
“…One study showed that probiotic treatment reduced the hippocampal oxidative stress (Chunchai et al, 2018). Five studies reported that probiotic supplementations attenuated oxidative enzymes (Sun et al, 2016;Alchujyan et al, 2018;Xu et al, 2018;Ramalho et al, 2019;Salami et al, 2019). Consistently, 4 studies showed that probiotic administration increases antioxidant activity (Divyashri et al, 2015;Huang et al, 2018;Ho et al, 2019;Roy Sarkar et al, 10.3389/fnins.2022.1065995 2020.…”
Section: Oxidant and Anti-oxidant Factorsmentioning
confidence: 92%